If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -14 = 6x + -11 + x Reorder the terms: -14 + 8x = 6x + -11 + x Reorder the terms: -14 + 8x = -11 + 6x + x Combine like terms: 6x + x = 7x -14 + 8x = -11 + 7x Solving -14 + 8x = -11 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -14 + 8x + -7x = -11 + 7x + -7x Combine like terms: 8x + -7x = 1x -14 + 1x = -11 + 7x + -7x Combine like terms: 7x + -7x = 0 -14 + 1x = -11 + 0 -14 + 1x = -11 Add '14' to each side of the equation. -14 + 14 + 1x = -11 + 14 Combine like terms: -14 + 14 = 0 0 + 1x = -11 + 14 1x = -11 + 14 Combine like terms: -11 + 14 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 8/15=x/45 | | x+12=-40 | | 15=10x+1.5x | | 20x-20=14x+22 | | 14/17=35/n | | x/8+7=24 | | -1-8(3x-4x)=31 | | 6a+14a=180 | | 48/-3 | | 4-8m=57 | | 5-9[2-(2y-8)]= | | 3x+1=4x+11 | | 2t+8=3t | | 8x^2-10xy+3y^2=0 | | 3/5(2x+13)=3(4-2x)+3 | | R/11 | | q+1/10=-3/5 | | -3d+5=7 | | a/6=-8 | | 5(-3+5x)=7 | | F+123/11=19 | | 12+3=30 | | 53=117-4r | | 6(4x-2)=3(8x+4) | | C-38/9=5 | | 15y-1=77 | | x-(-9/4)=5/7 | | (x-4)-(8-x)=2-(5x-9) | | 6(x+3)/5=3x-1 | | 2x^3+9x^2+13x+6=0 | | G-8/7=8 | | -3(4x-4)+6=-12x+18 |